Questions européennes - Jaquet, Pierre; Pisani-Ferry, Jean; Le Cacheux, Jacques; Atkinson, Tony; Boyer, Robert; Herzog, Philippe; Hel-Telier, Sylvie; Maurice, Joël; Ould Aoudia, Jacques; Tubiana, Laurence (Paris : La Documentation française, 2000)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: economische politiek; Europese Unie (EU).